The Influence of Transformational Leadership and Work Environment on Employee Morale at PT. Bank Riau Kepri Syariah Siak Sri Indrapura Branch - Hervina Amelia; Seno Andri; Mandataris (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze the effect of transformational leadership and the work environment on employee morale. This research was conducted at a banking company, namely PT. Bank Riau Kepri Syariah Siak Sri Indrapura Branch. This study uses 50 respondents who are all employees of PT. Bank Riau Kepri Syariah Siak Sri Indrapura Branch. In this study, the sampling technique used was Census/Total Sampling. Tests carried out in this study included validity tests, reliability tests, classic normality assumption tests, multicollinearity classic assumption tests, heteroscedasticity classic assumption tests, and hypothesis testing. The analytical tool used is multiple linear regression.